Legal standing of a legislative candidate from the same political party in an election dispute based on Constitutional Court Regulation No 2 of 2018 tied with the principle of justice - Pamungkas, Setioko Yudha; Tiopan, Demson (Technium Social Sciences Journal, 2021)
An election is a democratic system in which the public can choose its representative to sit within an institution. The Constitutional Court Regulation No 2 of 2018 regulates that in the case of candidates for membership in The House of Representative and the Regional Representative Assemble, a written permit from the secretary-general or the leader of the party is needed to obtain legal standing as a requirement regarding the dispute of electoral result. The research used the juridical-normative method that reviewed multiple literature works of secondary legal materials. The result of this research showed that the secretary-general or the leader of the party’s denial of a permit to file a plea at the Constitutional Court is an internal dispute in the party and it is not within the authority of the Constitutional Court to settle such dispute, but rather it is within the authority of the Political Party’s Court